Mapping the vulnerability of stunting in toddlers based on water, sanitation, and hygiene (WASH) indicators in South Sumatra Province by 2023: descriptive spatial analysis - Novitasari, Prihatini Dini; Utami, Putri; Prameswari, Ayu; Ambarwati, Dyah (BKM Public Health and Community Medicine, 2025)
Purpose: This study was conducted to map stunting vulnerability in children under five years of age by district/city based on stunting prevalence and WASH indicators. Methods: The research method employed was descriptive spatial analysis using a Geographic Information System (GIS) application with a scoring method, incorporating natural breaks in QGIS software. Results: As a result, Empat Lawang and South Ogan Komering Ulu districts are high-priority districts for an immediate response to stunting. Additionally, four districts/cities were classified as high-priority areas, three as medium-priority areas, five as low-priority areas, and three as very low-priority areas. Conclusion: Therefore, the government and communities are expected to increase efforts to prevent and handle stunting in children under five by prioritizing districts/cities with a very high level of vulnerability through expanding the availability of clean drinking water source and proper sanitation, and promoting clean and healthy living through optimal use of clean water and hand washing with soap.